Student writing : give it a generous reading - Spence, Lucy K. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
Education professionals interested in understanding student writing will want to read this book. It describes "Generous Reading," a novel method of approaching the writing of culturally and linguistically diverse students. This book addresses the increasing diversity present throughout schools across the U.S. and in other countries.Drawing from current research and theory in linguistics and composition, Spence has developed a way for teachers to tap into the cultural worlds of students and draw upon their linguistic understandings in order to help them improve their writing. The book is based on research projects conducted in the southwest and southeast regions of the United States. The chapters on language variation, culturally relevant instruction, and language transfer will also be of interest to writing teachers.Spence has presented the Generous Reading method across the nation and internationally where audiences have been eager to try out the methods in their classrooms with students of all ages. University professors have used Generous Reading in teacher education courses. This methodology has potential to change teachers' perspectives on student writing and illuminate writing strengths previously overlooked.